circlize implements and enhances circular visualization in R - Gu, Zuguang; Gu, Lei; Eils, Roland; Schlesner, Matthias; Brors, Benedikt (Bioinformatics, 2014)
Abstract. Summary: Circular layout is an efficient way for the visualization of huge amounts of genomic information. Here we present the circlize package, whic